Working and Living Conditions of Seasonal Workers in the Agro-processing sector: a Case study of Carara Agro-Processing Services (Pty) Ltd - Ngidi, Buyisiwe Sime (Rhodes University, Faculty of Humanities, Department of Sociology)
This thesis analyses the working and living conditions of seasonal workers. In the context of increased demand for processed and higher-value food products, the agro-processing industry has been identified as a main contributor in the South African labour market (Department of Agriculture, Forestry and Fisheries, 2012: 17). In an effort to achieve high production outputs while saving on operational costs, employers have been seen incorporating more non-standard labour. In the agro-processing industry, non-standard labour has been in the form of seasonal workers which has been a matter of concern to state structures tasked with ensuring company compliance with labour regulations, especially as it relates to the protection of workers within the industry. Many of these workers are offered little protection, sub-standard working conditions, irregular working hours, having little or no benefits, lacking skills and often facing a lack of trade union representation (Fourie, 2008:111). The introduction of section 198B of Labour Relations Act (LRA) has been designed to address the rights of non-standard workers and to provide protection against exploitative practices within various industries (Griessel, 2015:1). The thesis focuses its attention on the role of social reproduction and the labour process in perpetuating domination and inequalities within the workplace. Further, the thesis examines the challenges of non-standard labour and the difficulties of regulating it in practice. It also discusses the livelihood strategies adopted by seasonal workers when not employed, in this case, by Carara Agro Processing Services. The research adopted qualitative research techniques in the form of semi-structured interviews and used purposive and snowball sampling in accessing relevant data for analysis purposes.
Keywords: Seasonal labor -- South Africa; Labor market -- South Africa; Agricultural processing industries -- South Africa; Agricultural processing industry workers Employment -- South Africa; Employee rights -- South Africa; Unfair labor practices -- South Africa; South Africa. Labour Relations Act, 1995; Carara Agro-Processing Services (Firm)